2017
DOI: 10.1016/j.drudis.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Targeting amino acid metabolism for cancer therapy

Abstract: To support sustained biomass accumulation, tumor cells undergo metabolic reprogramming. Nutrient transporters and metabolic enzymes are regulated by the same oncogenic signals that drive cell-cycle progression. Some of the earliest cancer therapies used antimetabolites to disrupt tumor metabolism, and there is now renewed interest in developing drugs that target metabolic dependencies. Many cancers exhibit increased demand for specific amino acids, and become dependent on either an exogenous supply or upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
174
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(189 citation statements)
references
References 64 publications
1
174
0
5
Order By: Relevance
“…2,3 A Surveillance, Epidemiology, and End Results data analysis from 1975 to 2013 found that the 5-year relative survival rate of AA patients with BLCA was close to 66%, whereas European Americans (EAs) with BLCA had a survival rate close to 80%. 6 They also play a role in signal transduction, and their derivatives act as cofactors for many enzymes that play major roles in cancer progression. Emerging evidence suggests that both genetic and other biological factors play a role in racial disparities associated with BLCA; however, the poor survival of AA patients with BLCA is also due to late diagnoses and more aggressive tumor stages among AAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 A Surveillance, Epidemiology, and End Results data analysis from 1975 to 2013 found that the 5-year relative survival rate of AA patients with BLCA was close to 66%, whereas European Americans (EAs) with BLCA had a survival rate close to 80%. 6 They also play a role in signal transduction, and their derivatives act as cofactors for many enzymes that play major roles in cancer progression. Emerging evidence suggests that both genetic and other biological factors play a role in racial disparities associated with BLCA; however, the poor survival of AA patients with BLCA is also due to late diagnoses and more aggressive tumor stages among AAs.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids contribute to the biosynthesis of nucleotides, proteins, and lipids and the replenishment of tricarboxylic acid (TCA) cycle intermediates. 6 They also play a role in signal transduction, and their derivatives act as cofactors for many enzymes that play major roles in cancer progression. Among them is lysine demethylase 2A (KDM2A), which is an α-ketoglutaric acid-dependent, Jumonji C-containing histone demethylase Cancer March 15, 2019 that plays a crucial role in tumor progression through the suppression of matrix metalloproteinases (2, 9, 14, and 15).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in our knowledge of cancer metabolism suggest that targeting amino acid metabolism represents a promising strategy for the development of novel therapeutic agents (7). A traditional treatment that targets amino acids is L-asparaginase (ASNase).…”
mentioning
confidence: 99%
“…As nutrients, amino acids are required for protein synthesis, growth, and invasiveness of tumor cells . However, integrative screening of transcriptional regulators of amino acid metabolic genes in NB remains unknown.…”
Section: Discussionmentioning
confidence: 99%